Temperature Dependent Reactive Flow Model for Porous Explosives - Partom, Yehuda (European Journal of Applied Sciences, 2023)
Our temperature dependent reactive flow model (which we call TDRR) has not been designed to be first calibrated for a low porosity explosive, and then used for the same explosive but with a larger porosity. This is because the time scale of pore closure is expected to be much longer than that of the reaction. Here we upgrade our reactive flow model to take into account the time scale of the pore closure process. We do this by combining two of our previous models: 1) our rate dependent and gradual pore closure model, which we call PORT; and 2) our reactant temperature dependent reactive flow model, which we call TDRR. When a pressure wave passes through a computational cell of a porous explosive, it invokes two processes consecutively. These are: 1) rate dependent and gradual pore closure as in PORT, accompanied by temperature rise of the reactant; then, when ignition temperature is reached, 2) reactive burn of the reactant out of the pores, which act as hot spots, as in TDRR. We first describe the two models and how they are combined, and then we use the combined model to compute run to detonation in planar impact as function of the initial porosity.